Trends in pension saving among the long-term self-employed - Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2023)
The number of self-employed workers has been rising rapidly in the UK in recent decades. At the same time, private pension participation among this group has fallen sharply, leading to increasing concern among policymakers about the preparedness for retirement of self-employed workers. This report documents and analyses private pension saving using administrative data that follows the UK self-employed population over the decade from 2005-06 to 2014-15. We focus on a particular subset of the self-employed population, namely the working-age long-term self-employed (defined as those aged 22-64 who have been self-employed with no employment income for at least 5 years). We use a data set of Self Assessment tax returns, which self-employed workers have to submit each year to HM Revenue and Customs. We first document how the characteristics of the working-age long-term self-employed have changed over this period. We then focus on trends in pension participation and contribution amounts for this group of workers.
Keywords: 330; Employment and income; Savings; pensions and wealth; Ageing; Private pensions; Retirement; Savings; Employment; Tax